2016
DOI: 10.1136/annrheumdis-2016-eular.1287
|View full text |Cite
|
Sign up to set email alerts
|

OP0215 Subcutaneous Abatacept in Patients with Polyarticular Juvenile Idiopathic Arthritis and Inadequate Response To Biologic or Non-Biologic Disease-Modifying Antirheumatic Drugs: Pharmacokinetics, Efficacy and Safety

Abstract: BackgroundIV abatacept (ABA) 10 mg/kg every 4 weeks is safe and effective in reducing signs and symptoms of polyarticular forms of juvenile idiopathic arthritis (pJIA) in children and adolescents.1 SC ABA 125 mg weekly has therapeutically equivalent efficacy and comparable safety to IV ABA in adult RA, but similar data in pJIA are lacking.ObjectivesTo assess the PK, efficacy and safety of SC ABA in children and adolescents with active pJIA.MethodsThis single-arm, open-label (OL), Phase III study (NCT01844518) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Abatacept is approved for the treatment of rheumatoid arthritis (RA), juvenile idiopathic arthritis, and psoriatic arthritis in the United States and in Europe, and it has an established efficacy and safety profile ever since its initial approval in 2005 . Abatacept has consistently demonstrated efficacy benefits over placebo for clinical response, including reduced disease activity measures and improvements in physical function and health‐related quality of life . Clinical trials have also shown that abatacept is safe and well tolerated, with similar rates of adverse events (AEs) compared with placebo, demonstrating a favorable benefit‐risk profile .…”
Section: Introductionmentioning
confidence: 99%
“…Abatacept is approved for the treatment of rheumatoid arthritis (RA), juvenile idiopathic arthritis, and psoriatic arthritis in the United States and in Europe, and it has an established efficacy and safety profile ever since its initial approval in 2005 . Abatacept has consistently demonstrated efficacy benefits over placebo for clinical response, including reduced disease activity measures and improvements in physical function and health‐related quality of life . Clinical trials have also shown that abatacept is safe and well tolerated, with similar rates of adverse events (AEs) compared with placebo, demonstrating a favorable benefit‐risk profile .…”
Section: Introductionmentioning
confidence: 99%
“…Since the appropriate dosage for SC injections of abatacept has not been reported in animals, we extrapolated this based upon recommended doses used in human studies. Ruperto et al 16 injected children (10-25 kg body weight) diagnosed with juvenile idiopathic arthritis with 50 mg of abatacept. Thus 50 mg SC abatacept for a child weighing 10 kg corresponded to 0.125 mg weekly or 0.25 mg every other week for an average mouse weighing 25 g.…”
Section: Methodsmentioning
confidence: 99%
“…Since the appropriate dosage for SC injections of abatacept has not been reported in animals, we extrapolated this based upon recommended doses used in human studies. Ruperto et al[17] injected children (10-25kg body weight) diagnosed with juvenile idiophathic arthritis with 50mg of abatacept. Thus abatacept sc 50mg for child weighing 10 kg, corresponded to 0.125 mg weekly or 0.25 mg every other week for the average mouse weighing 25g.…”
Section: Methodsmentioning
confidence: 99%